PENGARUH KEPEMILIKAN PEMERINTAH, UKURAN KAP, DAN BOARD AGE TERHADAP PENGUNGKAPAN PENGENDALIAN - Totok Dewayanto (STIE Pelita Nusantara Semarang, 2020)
This study aims to examine the effect of government ownership, KAP size, and board age on disclosure of internal control. Company size is used as a control variable in this study. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2016 - 2017. This study used a sample of 226 companies using the purposive sampling method. The statistical technique used in this study is multiple linear regression. The results showed that government ownership had a positive and significant effect on disclosure of internal control, while board age had a negative and significant effect on disclosure on internal control. This study did not find any significant effect from KAP size on disclosure of internal control